2015
DOI: 10.1007/s40316-015-0027-5
|View full text |Cite
|
Sign up to set email alerts
|

Finite quotients of Galois pro- $$p$$ p groups and rigid fields

Abstract: For a prime number p, the author shows that if two certain canonical finite quotients of a finitely generated Bloch-Kato pro-p group G coincide, then G has a very simple structure, i.e., G is a p-adic analytic pro-p group (see Theorem 1). This result has a remarkable Galoistheoretic consequence: if the two corresponding canonical finite extensions of a field F-with F containing a primitive p-th root of unity-coincide, then F is p-rigid (see Corollary 1). The proof relies only on group-theoretic tools, and on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[14] To date,alimited number of photocontrollable HNO donors have been reported based on acyl nitroso intermediate formation by aretro-Diels-Alder reaction [9a-d] or the retrocycloaddition of a1 ,2,4-oxadiazole-4-oxide. [9a,e,f] Limitations of these HNO donors include photodecomposition in ambient light, [15] and/ or competition from NO formation, [9b-d] background thermal reactions,a nd secondary photocleavage processes. [16] Herein, we present the first in an ew family of photoactivatable N-alkoxysulfonamide HNO donors, 1,incorporating the well-characterized O-(3-hydroxy-2-naphthalenyl)methyl (HNM) photolabile protecting group.T he HNM group was selected as the phototrigger because of its rapid photocleavage (k release % 10 5 s À1 (t 1/2 % ms)) with good quantum and chemical yields.…”
mentioning
confidence: 99%
“…[14] To date,alimited number of photocontrollable HNO donors have been reported based on acyl nitroso intermediate formation by aretro-Diels-Alder reaction [9a-d] or the retrocycloaddition of a1 ,2,4-oxadiazole-4-oxide. [9a,e,f] Limitations of these HNO donors include photodecomposition in ambient light, [15] and/ or competition from NO formation, [9b-d] background thermal reactions,a nd secondary photocleavage processes. [16] Herein, we present the first in an ew family of photoactivatable N-alkoxysulfonamide HNO donors, 1,incorporating the well-characterized O-(3-hydroxy-2-naphthalenyl)methyl (HNM) photolabile protecting group.T he HNM group was selected as the phototrigger because of its rapid photocleavage (k release % 10 5 s À1 (t 1/2 % ms)) with good quantum and chemical yields.…”
mentioning
confidence: 99%
“…A crowded group of signals between δ = 7.5-8.5 ppm were attributed to the quinoline ring, whereas the bridged methylene gave two doublets at δ = 1.95 and 2.28 ppm. The yield of cycloadduct 14 are somewhat lower than usual for this kind of nitrosocarbonyl cycloaddition reactions, [8] and we could identify the regioisomeric 1,3-dipolar cycloadducts 15a and 15b as by-products, which were isolated in 23 and 18 % yields, respectively. The structures of cycloadducts 15a and 15b were determined on the basis of their analytical and spectroscopic data.…”
mentioning
confidence: 76%
“…By using the latter approach, Keck showed that the nitrosocarbonyl intermediates, thermally liberated from their HDA adducts with 9,10-dimethylanthracene in benzene at reflux, behave as active enophiles with various olefins in an ene-addition to afford adducts 4. [7] Recently, we developed two alternative routes to nitrosocarbonyl compounds 1 through the mild oxidation of nitrile oxides 5 with N-methylmorpholine N-oxide (NMO) [8] and the clean photolysis and thermolysis of 1,2,4oxadiazole-4-oxides 6. [9] The mild oxidation of nitrile oxide with NMO complements the HDA route and the ene-route, which works well with tetra-and tri-substituted alkenes.…”
mentioning
confidence: 99%